2021
DOI: 10.3390/healthcare9111403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Media Use on Depressive Symptoms in Older Adults with Self-Reported Hearing Impairment: An Empirical Study

Abstract: Older people with hearing impairment are more likely to develop depressive symptoms due to physical disability and loss of social communication. This study investigated the effects of social media on social relations, subjective aging, and depressive symptoms in these older adults based on the stimulus-organism-response (S-O-R) framework. It provides new empirical evidence to support improving the mental health and rebuilding the social relations of older people. A formal questionnaire was designed using the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…The main-effect model contends that social connections are advantageous regardless of one’s level of stress ( 60 ). For example, an empirical study based on the stimulus-organism-response (S-O-R) framework showed that social media use promotes strong social relationships among hearing-impaired older adults, as well as improving aging cognition and depressive symptoms ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main-effect model contends that social connections are advantageous regardless of one’s level of stress ( 60 ). For example, an empirical study based on the stimulus-organism-response (S-O-R) framework showed that social media use promotes strong social relationships among hearing-impaired older adults, as well as improving aging cognition and depressive symptoms ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, platforms like TikTok and Kwai facilitate access to external information and entertainment through short videos. Secondly, according to the social causation theory [30], older individuals are inclined to use social media to garner social capital from robust o ine relationships, thereby mitigating serious mental health issues [31]. Thirdly, these platforms enhance the social structure for older adults, enabling communication with a wider network [32], and providing an anonymous space for safe emotional expression and increased social participation through bullet chatting [33].…”
Section: Online Media Use and Mental Healthmentioning
confidence: 99%
“…Seven studies were excluded either as the study outcomes were not relevant to the scope of this review (Ma et al, 2021;van Wier et al, 2021;Wong et al, 2016;Giordano et al, 2021;Oh et al, 2022) or the non-peer-reviewed publications (Choudhury & Renken, 2018;O'Brien et al, 2019). Thus, a total of 19 studies were included in the present systematic review.…”
Section: Study Selectionmentioning
confidence: 99%